Stromal Caveolin-1 and Caveolin-2 Expression in Primary Tumors and Lymph Node Metastases. (10th April 2018) - Gerstenberger, Wladimir; Wrage, Michaela; Kettunen, Eeva; Pantel, Klaus; Anttila, Sisko; Steurer, Stefan; Wikman, Harriet
Abstract : The expression of caveolin-1 (CAV1) in both tumor cell and cancer-associated fibroblasts (CAFs) has been found to correlate with tumor aggressiveness in different epithelial tumor entities, whereas less is known for caveolin-2 (CAV2). The aim of this study was to investigate the clinicopathological significance and prognostic value of stromal CAV1 and CAV2 expression in lung cancer. The expression of these two genes was investigated at protein level on a tissue microarray (TMA) consisting of 161 primary tumor samples. 50.7% of squamous cell lung cancer (SCC) tumors showed strong expression of CAV1 in the tumor-associated stromal cells, whereas only 15.1% of adenocarcinomas (AC) showed a strong CAV1 expression (p < 0.01 ). A strong CAV2 stromal expression was found in 46.0% of the lung tumor specimens, with no significant difference between the subtypes. Neither CAV1 nor CAV2 stromal expression was associated with any other clinicopathological factor including survival. When the stromal expression in matched primary tumors and lymph node metastases was compared, both CAV1 and CAV2 expressions were frequently found lost in the corresponding stroma of the lymph node metastasis (40.6%, p = 0.003 and 38.4%, p = 0.001, resp.). Loss of stromal CAV2 in the lymph node metastases was also significantly associated with earlier death (p = 0.011 ). In conclusion, in contrast to the expression patterns in the tumor tissue of lung cancer, stromal expression of CAV1 in primary tumors was not associated with clinical outcome whereas the stromal expression of especially CAV2 in the metastatic lymph nodes could be associated with lung cancer pathogenesis.